Eprenetapopt Plus Azacitidine in TP53-Mutated Myelodysplastic Syndromes and Acute Myeloid Leukemia: A Phase II Study by the Groupe Francophone des Myélodysplasies (GFM). Issue 14 (10th May 2021) - Cluzeau, Thomas; Sebert, Marie; Rahmé, Ramy; Cuzzubbo, Stefania; Lehmann-Che, Jacqueline; Madelaine, Isabelle; Peterlin, Pierre; Bève, Blandine; Attalah, Habiba; Chermat, Fatiha; Miekoutima, Elsa; Rauzy, Odile Beyne; et al.
Abstract : PURPOSE: TP53 -mutated ( TP53m ) myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) have very poor outcome irrespective of the treatment received, including 40% responses (20% complete remission [CR]) with azacitidine (AZA) alone, short response duration, and a median overall survival (OS) of approximately 6 months. Eprenetapopt (APR-246), a novel first-in-class drug, leads to p53 protein reconformation and reactivates its proapoptotic and cell-cycle arrest functions. PATIENTS AND METHODS: This phase II study assessed the safety and efficacy of eprenetapopt in combination with AZA in untreated high or very high International Prognostic Scoring System-R TP53m MDS and AML patients. RESULTS: Fifty-two TP53m patients (34 MDS, 18 AML [including seven with more than 30% blasts]) were enrolled. In MDS, we observed an overall response rate (ORR) of 62%, including 47% CR, with a median duration of response at 10.4 months. In AML, the ORR was 33% including 17% CR (27% and 0% CR in AML with less than and more than 30% marrow blasts, respectively). Seventy-three percent of responders achieved TP53 next-generation sequencing negativity (ie, variant allele frequency < 5%). The main treatment-related adverse events were febrile neutropenia (36%) and neurologic adverse events (40%), the latter correlating with a lower glomerular filtration rate at treatment onset ( P < .01) and higher age ( P = .05), and resolving with temporary drug interruption without recurrence after adequate eprenetapopt dose reduction. With a median follow-up of 9.7 months, median OS was 12.1 months in MDS, and 13.9 and 3.0 months in AML with less than and more than 30% marrow blasts, respectively. CONCLUSION: In this very high-risk population of TP53m MDS and AML patients, eprenetapopt combined with AZA was safe and showed potentially higher ORR and CR rate, and longer OS than reported with AZA alone.